(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The study aimed to assess poultry farmers‘ (PF) knowledge, attitudes, and practices (KAP) about the utilization of vaccines for the prevention of infectious illnesses. Materials and Methods: A cross-sectional investigation was carried out involving 260 respondents in the northern area of Bangladesh. Data were collected by structured questionnaires with randomly selected participants. The analysis used descriptive statistics and logistic regression. Results: Most respondents were male (81.5%), aged 31–40 years (32.3%), with secondary education (27.7%), as well as vaccination training (30.8%). Although 63.1% of participants were aware of immunizations, only 41.5% recognized they prevented zoonotic infections, and 66.9% reduced antibiotic use. Remarkably, 67.7% knew about the bad effects, and 70.8% said they are vaccinating their chicken flocks. Overall, 41.5%, 48.5%, and 29.2% of the farmers demonstrated good knowledge and a positive attitude, as well as performed better practices. Multivariable analyses found that male farmers aged over 50 years with 3–5 years of broiler farming expertise and having undergone vaccination training demonstrated a higher likelihood of possessing substantial knowledge regarding vaccine utilization. Accordingly, favorable attitudes were connected with male farmers aged over 50 years and having 3–5 years of broiler farming experience. Farmers who engaged in broiler farming demonstrated a higher likelihood of exhibiting effective vaccination practices only. Conclusion: The study highlights gaps in farmers‘ KAP related to vaccine usage. It is essential to create targeted educational as well as training programs to effectively address these gaps and prevent possible poultry illnesses. J. Adv. Vet. Anim. Res., 12(3): 817–831, September 2025 http://doi.org/10.5455/javar.2025.l944